HARTA DALAM PERSPEKTIF AL-QUR’AN - Ma’u, Dahlia Haliah (The Pontianak State Institute of Islamic Studies, 2013)
Islam is very responsive to human desires in term of property ownership. This can be understood from a number of the verses of the Koran that mention the word property, both in the singular or plural. If understood correctly, the verses that mention property obviously show How Islam views property which in essence is the spirit of Islamic teachings to build a rich community. The Qur’an also affirms that any Muslim who legitimately has a certain property, has the right to use it in accordance with the rules outlined by Allah. In this case the Qur’an recommends that any individual or group do some things related to the property they own, namely: Donate, develop, and distribute it. Besides that they also have to perform a social function of the property they own, which include a infak, sadaqah, grants, charity, and endowments.